Ghrelin, anthropometry and nutritional assessment in geriatric hospital patients - Sieber, Cornel; et al. (Zeitschrift für Gerontologie und Geriatrie, 2007)
Loss of appetite is an important causal factor for malnutrition in the elderly, and age-associated changes of hormone levels seem to be of great relevance in this regard. At present there has been no study exploring the role of the appetite stimulating hormone ghrelin in geriatric hospital patients. Study population 121 (f 82, m 39) patients from two geriatric wards of our hospital. Mean age was 80.2 +/- 7.7 years. Results The basal ghrelin level (mean 158.43 +/- 144.02 pg/ml) showed no gender difference. No association with the age of the patients could be demonstrated. There was an inverse correlation of basal ghrelin with BMI, upper arm circumference, triceps skin fold, basal leptin and insulin. No correlation between established screening/assessment tools for malnutrition - Mini Nutritional Assessment (MNA), Subjective Global Assessment (SGA), Nutritional Risk Screening (NRS) - could be shown. Even after grouping the ghrelin levels into six different disease categories, no significant difference could be shown between them. Conclusion For our patients aged 67 to 94, no correlation with age could be shown. Nevertheless the basal level of ghrelin is substantially lower when compared to a younger population with similar BMI, while the anorectic hormone leptin shows no substantial difference. This causes a more anorectic hormonal constellation which may contribute to the loss of appetite in geriatric patients.
Keywords: ghrelin; appetite regulation; geriatric patients; Mini Nutritional Assessment; Nutritional Risk Screening